(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The Pradhan Mantri Mudra Yojana (PMMY), launched in April 2015, is a transformative financial inclusion initiative designed to empower India's vast informal enterprise sector by providing collateral-free institutional credit. This study conducts a comprehensive economic evaluation of PMMY’s impact on Micro, Small, and Medium Enterprises (MSMEs) in Karnataka, with an in-depth empirical focus on Mandya District. Utilizing a mixed-method research design that synthesizes primary field data from 60 MSME beneficiaries with secondary sources, the analysis assesses changes in key performance indicators: capital formation, turnover, employment, income levels, and financial integration. The findings demonstrate that PMMY has been instrumental in driving enterprise growth, facilitating job creation, enhancing incomes, and reducing reliance on informal credit. However, the study also identifies persistent structural challenges, including procedural inefficiencies, limited financial literacy, and insufficient post-loan support mechanisms, which constrain the scheme's full developmental potential. The paper concludes that while PMMY stands as a critical pillar for inclusive and regional economic growth, its long-term success necessitates institutional strengthening and integrated entrepreneurial ecosystem support